Cross Platform Analysis of Volatile Organic Compounds Using Selected Ion Flow Tube and Proton-Transfer-Reaction Mass Spectrometry - Lin, Geng-Ping; Vadhwana, Bhamini; Belluomo, Ilaria; Boshier, Piers R; Španěl, Patrik; Hanna, George B (Journal of the American Society for Mass Spectrometry, 2021)
Volatile breath metabolites serve as potential disease biomarkers. Online mass spectrometry (MS) presents real-time quantification of breath volatile organic compounds (VOCs). The study aims to assess the relationship between two online analytical mass spectrometry techniques in the quantification of target breath metabolites: selected ion flow tube mass spectrometry (SIFT-MS) and proton-transfer-reaction time-of-flight mass spectrometry (PTR-ToF-MS). The two following techniques were employed: (i) direct injection with bag sampling using SIFT-MS and PTR-ToF-MS and (ii) direct injection and thermal desorption (TD) tube comparison using PTR-ToF-MS. The concentration of abundant breath metabolites, acetone and isoprene, demonstrated a strong positive linear correlation between both mass spectrometry techniques (r = 0.97, r = 0.89, respectively; p < 0.001) and between direct injection and TD tube (r = 0.97, r = 0.92, respectively; p < 0.001) breath sampling techniques. This was reflected for the majority of short chain fatty acids and alcohols tested (r > 0.80, p < 0.001). Analyte concentrations were notably higher with the direct injection of a sampling bag compared to the TD method. All metabolites produced a high degree of agreement in the detection range of VOCs between SIFT-MS and PTR-ToF-MS, with the majority of compounds falling within 95% of the limits of agreement with Bland-Altman analysis. The cross platform analysis of exhaled breath demonstrates strong positive correlation coefficients, linear regression, and agreement in target metabolite detection rates between both breath sampling techniques. The study demonstrates the transferability of using data outputs between SIFT-MS and PTR-ToF-MS. It supports the implementation of a TD platform in multi-site studies for breath biomarker research in order to facilitate sample transport between clinics and the laboratory.
Keywords: butadieny; aceton; Male; direct injection; Butadienes; dechové testy; Acetone; Hemiterpenes; Adult; volatile organic compound; dospělí; mužské pohlaví; Mass Spectrometry; hemiterpeny; Breath Tests; thermal desorption: PTR-ToF-MS; lidé; ženské pohlaví; těkavé organické sloučeniny; Humans; Volatile Organic Compounds; hmotnostní spektrometrie; breath analysis; SIFT-MS; Female